Pengaruh Kualitas Pelayanan terhadap Kepuasan Pelanggan Indihome Fiber pada PT.Telkom Kota Palangka Raya Provinsi Kalimantan Tengah - Muhamad Yusuf; Silvia Nika (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2017)
The purpose of this study was to determine how much influence the Service Quality on Indihome Fiber Customer Satisfaction At PT Telkom Telangka Raya Province of Central Kalimantan. The method used in this study is a quantitative method. Data collection techniques using questionnaires (questionnaires), the number of samples in this study were 332 Indihome fiber customers in the City of Palangka Raya. The sampling technique is using Random Sampling techniques or random samples and the analysis technique used to process data is by-product moment correlation analysis techniques. The results of the analysis using Product Moment obtained a Rxy value of 0.984. This value is compared with the table value about the interpretation included in the very strong category. This value is between 0.80-1,000, this shows that Service Quality has a real and positive influence on Indihome Fiber Customer Satisfaction at PT Telkom Telangka Raya City of Central Kalimantan Province.